2015
DOI: 10.3402/meo.v20.28453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tailored feedback in assessment of communication skills for medical students

Abstract: BackgroundFinding out the effective ways of teaching and assessing communication skills remain a challenging part of medication education. This study aims at exploring the usefulness and effectiveness of having additional feedback using qualitative analysis in assessment of communication skills in undergraduate medical training. We also determined the possibilities of using qualitative analysis in developing tailored strategies for improvement in communication skills training.MethodsThis study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The sixth co-word cluster contained terms of measurement contents (“communication”, “physician-patient relations”) and methods (“patient simulation”). These three high-frequency terms occurred simultaneously in the articles, revealing that researchers were interested in the relationship between patients and medical students, especially the assessment of communication skills by patient simulation [ 19 ]. From the above results, six hotspots of clinical competence measurement were found, as follows: [ 1 ] the impact of curriculums on clinical competence, [ 2 ] development of new methods of clinical competence measurement, [ 3 ] students’ feedback on clinical competence measurement, [ 4 ] the effect of computer simulation training on clinical competence, [ 5 ] students’ clinical performance in the important steps of learning, and [ 6 ] communication skills measured by patient simulation.…”
Section: Resultsmentioning
confidence: 99%
“…The sixth co-word cluster contained terms of measurement contents (“communication”, “physician-patient relations”) and methods (“patient simulation”). These three high-frequency terms occurred simultaneously in the articles, revealing that researchers were interested in the relationship between patients and medical students, especially the assessment of communication skills by patient simulation [ 19 ]. From the above results, six hotspots of clinical competence measurement were found, as follows: [ 1 ] the impact of curriculums on clinical competence, [ 2 ] development of new methods of clinical competence measurement, [ 3 ] students’ feedback on clinical competence measurement, [ 4 ] the effect of computer simulation training on clinical competence, [ 5 ] students’ clinical performance in the important steps of learning, and [ 6 ] communication skills measured by patient simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Application of emotional intelligence could also avoid “negative emotional reactions such as denial and defense,” experienced by some of the teachers in Jamshidian et al’s study,1 and allow clinical teachers to reflect on feedback content objectively. The delivery of additional feedback using qualitative analysis has also improved the level of acceptance of feedback in medical students 5. Such tailoring and personalization of feedback to the recipients’ traits may reduce the likelihood of emotional volatility, create a positive environment, and strengthen the quality of feedback and mutual respect and understanding between provider and recipient, to increase learning and improve patient care.…”
Section: Dear Editormentioning
confidence: 99%
“…Video-based feedback has been researched previously at our institution to evaluate its effectiveness in teaching medical students. In this context, studies found that video annotated feedback helped students identify specific areas of strength and weakness and increased the overall acceptance of scores [6, 9]. Additional research has demonstrated positive outcomes in the use of video-based assessments of medical students by physician mentors, including enrichment of students’ learning from clinical settings, exposure of students to a larger number of mentors, and improving the ability of students to recall their own performances [10].…”
Section: Introductionmentioning
confidence: 99%